THE EFFECT OF WORKING CAPITAL TURNOVER AND INVENTORY TURNOVER ON PROFITABILITY (ON THE TEXTILE AND GARMENT SECTOR MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE) - Wairooy, Muhamad Ali (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study aims to examine and analyze the effect of working capital turnover and limited profitability turnover on textile and garment sector manufacturing companies listed on the Indonesia Stock Exchange. Data collection uses secondary data using saturated sample techniques (census). The population is all textile and garment sector manufacturing companies listed on the Indonesia Stock Exchange during the 2012-2015 period of 12 companies, while the sample taken for the number of observations in this study for 3 years, the number of observations of this study was 12 x 3 years = 36 samples . The data obtained were analyzed using multiple linear regression analysis, F test, t test and test coefficient of determination (R²) which was carried out using the SPSS version 20. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that working capital turnover has a positive and significant effect on profitability, Inventory turnover has a positive and significant effect on profitability, and working capital turnover and inventory turnover simultaneouslypositive and significant effect on profitability.